THE MAIN COMPONENTS EXPRESSING THE MEANING OF THE SEME “CHARACTER” IN ENGLISH PHRASEOLOGICAL UNITS (Scientific journal of the Fergana State University, 2025)
The study of English phraseological units (PU) offers valuable insights into the relationship between language and the expression of human experience, particularly in the representation of character. Phraseological units are fixed, idiomatic expressions that often reflect cultural values, psychological tendencies, and societal norms. This paper explores the basic components that express "character" within English phraseological units, categorizing them into four main components: physical traits, psychological attributes, behavioral patterns, and social roles. The research aims to uncover how these components are intertwined in the construction of meaning in such expressions, thereby offering a deeper understanding of how language reflects human nature and societal perspectives.